Application of SBAR Communication in the Implementation of Nurse Weigh-in in the Inpatient Room of Dr. M.M Dunda Limboto Hospital - Sabirin B. Syukur; Fadli Syamsuddin; Anggun Yudistira Hunow (PROMOTOR, 2023)
The use of good communication techniques during weigh-ins is important in improving patient safety. SBAR communication is a communication technique recommended by JCI to be used in the implementation of weigh-ins to improve patient safety in hospitals. The purpose of this study was to determine the relationship between SBAR communication and the implementation of nurse weighing in the Inpatient Room of Dr. M.M Dunda Hospital. This research method is quantitative research with a descriptive research design using a cross-sectional design. Data collection was carried out using questionnaire sheets with a population of 35 respondents. The number of respondents was taken using purposive sampling techniques. The data obtained were processed statistically using the Fisher's Exact Test. The results showed that there was a relationship between SBAR communication and the implementation of weigh-in in the Inpatient Room of Dr. M.M Dunda Limboto Hospital with a p-value result of 0.000. In conclusion, there is a relationship between SBAR communication and the implementation of nurse weighing in the Inpatient Room of Dr. M.M Dunda Limboto Hospital (p-value < 0.05). Advice for nurses is expected that nurses always use complete SBAR communication in the implementation of weigh-ins at every shift change.